Cost of hospitalization of children with rotavirus infection in a research and training hospital [Bir eǧitim ve araştırma hastanesindeki rotavirüslü çocuklarda yatış maliyeti] - (:unkn) unknown (AVES, 2011)
Objective: Pharmacoeconomic analyses of rotavirus routine vaccination program have been conducted in many countries due to the critical economic burden of rotavirus infections. The aim of this study was to estimate the cost of hospitalization for children with rotavirus infections. Material and Methods: In this retrospective study, the discharge invoices of 215 inpatients (aged between 1 month and 5 years) hospitalized for treatment of rotavirus infection in ŞiŞli Etfal Research and Training Hospital between April 1, 2008 and March 31, 2009 were evaluated. Only direct medical costs were considered in the analysis. Results: The mean hospital stay of 215 patients was calculated as 3.74±2.84 days and mean of direct medical cost was calculated as 151 USD per patient. While 33 USD of the average total direct cost was related to drug therapy, the remaining costs were bed, medical supplies, laboratory tests and venture expenses. In our comparison based on the manufacturer list price in Turkey (152 USD for Rotateq®, and 126 USD for Rotarix® per a vaccine series), the prices of vaccines were found higher than the prices that were proposed for cost savings by studes in other countries. Conclusion: Only the cost of hospitalization due to rotavirus infections was analyzed in this study. However, additional costs of non-hospitalized patients should not be ignored. In order to include rotavirus vaccine into the national vaccination pro- gram, large scale cost-effectiveness analyses are needed. We believe that reducing vaccine prices as well as informing parents by health care providers may contribute to increasing of vaccination rates, which is important in the prevention of rotavirus infections.
Keywords: Cost; Diarrhea; Hospitalization; Rotavirus; Vaccination